ANALISIS SISTEM ANTRIAN DALAM OPTIMALISASI LAYANAN DI SUPERMARKET HYPERSTORE - Benediktus L V Bataona; Antonio E.L. Nyoko; Ni Putu Nursiani (Journal of Management Small and Medium Enterprises (SMEs), 2020)
The purpose of this study is to determine the average customer arrival level and average service level at the Hyperstore Supermarket and analyze the queuing system by optimizing the number of cashiers that must be set at the Hyperstore Supermarket. The results showed that the queuing model used at the Hyperstore Supermarket is Multi Channel Single Phase by applying the First Come First Serve (FCFS) queuing discipline. The average service level at the Hyperstore Supermarket is 146 people/hour. The current number of lines opened at the Hyperstore Supermarket is 6 cashiers. However, 6 cashier lines are excess even though 3 cashier lines are sufficient. Queue system analysis shows that the optimal number of cashier lines which is 1 cashier line open at 3:00 pm to 4:00, 2 cashier lines open at 16:00 to 19:00 and 3 cashiers lines opened at 19:00 to 20:00 Keywords: Queue Theory, Multiple Line Queue Model, Cashier, Service Optimization